Staynomic: The Near One, The Easy one, The Small One - Riyono Gede Trisoko; Elti Martina; Sri Febrina (Conference Series, 2021)
Currently, the pandemic is still an unavoidable part or close to us. Everything is related to service businesses, especially tourism, will have an impact. Therefore, this is critical to address it as information and an effort to provide solutions for the development of tourism service businesses significantly affected by the spread of this virus. Services in the developed theories like the Soul of service say [1] it represents a creation of taste from an activity. In the Soul of service, the taste is rooted in the sense of security and comfort. It requires much consideration in the development of the affected tourism business. Through this paper, the author tries to provide solutions for the development of tourism service businesses by observing the socio-economic situation and subsequently employing an analogy and developing it into several existing social theories. Hence, it enhances a tourism development concept during this pandemic.